'I Search for the Channel Made Fragrant by the Maile': Genealogies of Discontent and Hope. Issue 3 (November 2014) - Tengan, Ty P. Kāwika; Roy, Lamakū Mikahala; Pickles, Anthony J
Abstract Ahu'ena Heiau (whose name Burning Altar describes the sacredness of light) is deemed a paramount religious temple rededicated to Lono by Kamehameha the Great at Kamakahonu, the first Capital of the Hawaiian Kingdom. Restored in 1975 under the leadership of Kahu David Kahelemauna Roy, Jr., it is a place honoured by Kānaka 'Ōiwi (Indigenous Hawaiians) in ways not recognized by the King Kamehameha Kona Beach Hotel on whose ground it now sits. Henry E. P. Kekahuna, noted Hawaiian scholar, produced a series of maps in the 1950s that documented this heiau (traditional place of ceremony) and other significant cultural sites. Kekahuna's maps reveal a complex, contested landscape of overlapping contemporary and historic features, many of the latter invisible yet still alive in local hearts and memory. The Association for Social Anthropology in Oceania (and indeed anthropology at large) has analogously complex relations with the communities and the region it claims as its particular field of knowledge. The 2014 annual meeting, which convened in the Kamehameha Kona Beach Hotel, provokes a critical assessment of academic practice in light of Indigenous sovereignty, genealogy, senses, memory, and place.